Reviews. Jacob King (ed.), Scottish Gaelic Place-names: The Collected Works of Charles M. Robertson 1864–1927 (Sleat, Isle of Skye: Clò Ainmean-Àite na h-Alba, 2019), xxxvi + 554 pp. £19.99 paperback. ISBN 9781721806874. (2019) - Evemalm, Sofia
No abstract available